A content‐dependent Daltonization algorithm for colour vision deficiencies based on lightness and chroma information. Issue 4 (30th December 2020) - Shen, Xuming; Feng, Jianhua; Zhang, Xiandou
Abstract: To help CVD (colour vision deficiency) observers distinguish among different colours in digital images, this study proposes a content‐dependent Daltonization algorithm based on lightness and chroma information. This improves the trade‐offs in contrast, naturalness, and colour consistency deficiencies found in existing methods. Chroma remapping and brightness adjustments on image content are utilized to increase contrast and maximize the preservation of the original hue. In a quantitative study, the proposed method proved more useful for dichromats than did existing methods. The evaluation by research subjects showed that the method was superior to the current methods in balancing contrast, naturalness, and colour consistency.